BaPEMBEBASAN NARAPIDANA DALAM PERSPEKTIF KONSEP ASIMILASI DI MASA PANDEMI COVID 19has Indonesia - Sahat Maruli Tua Situmeang (JURNAL LITIGASI (e-Journal), 2020)
The Second Principle of Pancasila stating "just and civilized humanity", ensuring that Indonesian people are treated fairly and in a civilized manner despite their status as convicted felon. In addition, in the fifth principle, it is stated that "social justice for all Indonesian people" means that even as a prisoner, they are entitled to get their rights just like normal human life. During the Covid-19 pandemic, the government issued a policy of releasing prisoners through an assimilation program. With this policy, the public is worried that convicts who are released will commit crimes again. Based on this background, the problem is how the concept of assimilation is viewed from the perspective of criminal theory and whether the assimilation policy during the Covid-19 pandemic is in accordance with the concept of assimilation. In analyzing, the normative juridical method using the statue method of approach is used. The types of legal materials used are primary legal materials in the form of related laws and regulations and secondary legal materials in the form of books and scientific articles. Based on the results of the research, it shows that the concept of assimilation viewed from the perspective of integrative theory of sentencing is considered inappropriate because the purpose of punishment is to maintain legal order in society and improve the personality of the perpetrator while still paying attention to human rights (HAM) compared to imprisonment which causes more negative impacts and The assimilation policy during the Covi-19 pandemic was in accordance with the concept of assimilation, namely by fulfilling the requirements and conditions as stipulated in the laws and regulations, but researchers argue that the policy should be accompanied by reconstruction and / or reformulation related to the criminal system through the application of social work criminal sanctions as well as prevention and overcoming of crime through restorative justice. Keywords: Assimilation, Covid-19, Law enforcement.